Ex-Migrant Workers’ Sisterhood: Case Study on ‘Desbumi’ and ‘Desmigratif’ Programs in Wonosobo District - Zulyani Evi; Yovi Arista; Safina Maulida; Arief Rahadian (Jurnal Perempuan, 2020)
Ex-migrant workers are often found dealing with the lack of union that could cater their needs. These people that are mostly female are often excluded from the process of decision making in their own villages. In 2013, a program from civil society organization called Desbumi (Desa Peduli Buruh Migran or Migrant Workers Care Village) Initiative was launched in Wonosobo District, with the aim to improve migrant workers’ living conditions - especially female - through empowering female ex-migrant workers group. In 2016, a similar program called Desmigratif (Desa Migran Produktif or Productive Migrants Village) Initiative was spearheaded by the Ministry of Manpower, which shares the same goal with Desbumi Initiative. Building upon the debates surrounding the concept of sisterhood provided by Bell Hooks and Robin Morgan, this study discusses whether the top-down approach in organizing female ex-migrant workers residing in Kuripan, Lipursari, Rogojati, and Sindupaten Village through Desbumi and Desmigratif initiative could result in any forms of sisterhood formed during the implementation of the programs, and challenges that they faced along the way. This study found that characteristics associated with sisterhood of friendships were apparent in all female ex-migrant groups, signified by mutual support among women, shared experience, journey of self-discovery, and collective identity built upon similarities. On the discussion of challenges, several obstacles such as lack of regeneration, women’s domestic burden, and the issue of sustainability appeared along the journey of the sisterhood of ex-migrant workers.